2016
DOI: 10.2196/games.5997
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Validity of a Computer-Based Game to Assess Cognitive Processes, Reward Mechanisms, and Time Perception in Children Aged 4-8 Years

Abstract: BackgroundA computer-based game, named Timo’s Adventure, was developed to assess specific cognitive functions (eg, attention, planning, and working memory), time perception, and reward mechanisms in young school-aged children. The game consists of 6 mini-games embedded in a story line and includes fantasy elements to enhance motivation.ObjectiveThe aim of this study was to investigate the validity of Timo’s Adventure in normally developing children and in children with attention-deficit/hyperactivity disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Several studies support the notion that SGs could help children, in particular those with ADHD, in improving attention abilities and executive functions [31]: e.g., CogMed©, a computerized training program [32]; PlayMancer (with the inclusion of biosignal data) [33]; Harvest Challenge BCI videogame, with the measurement of cerebral signals [34]; Virtual Classroom [35]; Plan-it Commander [36]; Boogies Academy; and Cuibrain [37]. Other studies highlight that SGs (e.g., Timo's Adventures [38]) could be useful to assess the abilities of young children with ADHD (cognitive function, reward mechanisms, and time perception). Some SGs include neurofeedback systems; It has been shown that these improve executive control in subjects with ADHD in combination with pharmacological treatment [39].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support the notion that SGs could help children, in particular those with ADHD, in improving attention abilities and executive functions [31]: e.g., CogMed©, a computerized training program [32]; PlayMancer (with the inclusion of biosignal data) [33]; Harvest Challenge BCI videogame, with the measurement of cerebral signals [34]; Virtual Classroom [35]; Plan-it Commander [36]; Boogies Academy; and Cuibrain [37]. Other studies highlight that SGs (e.g., Timo's Adventures [38]) could be useful to assess the abilities of young children with ADHD (cognitive function, reward mechanisms, and time perception). Some SGs include neurofeedback systems; It has been shown that these improve executive control in subjects with ADHD in combination with pharmacological treatment [39].…”
Section: Introductionmentioning
confidence: 99%
“…Although the toolbox and other app versions of psychometric tests are well described [7,15,16], little has been written about how other mother and child assessment methodologies can benefit in a similar way from technological progress. Naturalistic observation, caregiver and clinical interviews, direct assessment, and coding of interactions are still primarily the global tools of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, assessments of symptoms of developmental disorders such as Autism Spectrum Disorders (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) have been gamified [30,31]. There is also some indication that these games might be able to provide metrics that are potentially sensitive to measuring change brought about through interventions [32].…”
Section: Introductionmentioning
confidence: 99%